Transformative Education Related to Ethno-Religion, Digital Technology, and Global Awareness - Ibanga, Isaac John; Onwuka, Immaculater Akudo; Garba, Zakariyau (The Indonesian Institute of Science and Technology Research, 2024)
In our rapidly evolving world, transformative education emerges as a critical necessity, particularly concerning ethno-religion, digital technology, and global awareness. This study delves into the intersectionality of these factors and their influence on education, aiming to equip individuals to navigate and thrive in an increasingly diverse and interconnected global society. Through a literature review, we explore the multifaceted dimensions of transformative education, emphasizing its relevance to ethno-religion, digital technology, and global awareness. The integration of digital technology in transformative education has revolutionized learning experiences, offering innovative tools for collaboration, research, and communication. However, it is imperative to ensure equitable access and address challenges related to digital literacy and cyber ethics. Global awareness in transformative education extends beyond exposure to different cultures, aiming to cultivate empathy, solidarity, and critical analysis of global issues. By engaging with real-world challenges and diverse perspectives, students can develop into informed and engaged global citizens. Employing a narrative-style research design, this study integrates subjective opinions, literature support, thematic analysis, and insights from the educational field to provide a comprehensive understanding of transformative education's potential to shape empathetic, critically aware individuals prepared to address complex global challenges. Through exploration of pedagogical strategies, case studies, and best practices, the study aims to contribute to inclusive and equitable educational environments conducive to transformative learning.